Pengaruh Corporate Social Responsibility dan Capital Intensity terhadap Tax Avoidance dengan Sales Growth Sebagai Variabel Moderasi - Mohammad Sobarudin; Endang Ruhiyat (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2022)
This study aims to examine and provide empirical evidence regarding the effect of corporate social responsibility and capital intensity on tax avoidance with sales growth as a moderating variable in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2015-2020 period. The type of research used is quantitative research. The number of samples used in this study whereas 150 data from 25 manufacturing companies in the consumer goods industry during the period of 2015-2020 period, which was obtained using the purposive sampling method based on predetermined criteria. The data used is was secondary data in the form of audited annual financial reports for the 2015-2020 period obtained from the official website Indonesia Stock Exchange and the websites of each company. The data analysis technique used is as descriptive statistics and panel data regression analysis using Eviews 9 software. The results of this study were based on a partial test with a t test-test stating that corporate social responsibility has an effect on tax avoidance. In contrast, capital intensity has no effect on tax avoidance. Based on the simultaneous test, the F test states stated that simultaneously corporate social responsibility and capital intensity affect the practice of tax avoidance. Based on the interaction or moderation test, the MRA test stated that sales growth did not moderate the relationship between CSR and tax avoidance or the relationship between capital intensity and tax avoidance.